(untitled) (Journal of Informatics Education and Research, 2023)
For most of the employees across the globe, the COVID -19’s impact has been dependent on answering one question i.e. Can I continue with my current job in the work from home mode or am I bound to my workplace only? The corona virus has broken all cultural and technological barriers that prevented remote work as an option in the past. Lockdown, quarantines, self- isolation etc. has forced millions of employees and companies to experiment and adopt work from home scenarios. The likelihood of adopting a work from home mode largely depends on the extent of physical, spatial and interpersonal requirements associated with the job. Even though many jobs related to gathering and analysis of data and information, finance, insurance, teaching, counselling etc. can be done remotely. But there are many jobs that require physical presence and use of fixed equipment like in case of CT-scans, production of finished goods, processing customer transactions in retail stores, physiotherapy, surgery etc. Such jobs can’t be performed remotely. It has been found that the potential for remote work is highly concentrated among highly skilled and highly qualified workforce in limited industries and occupations. More than half of the workforce that belongs to low paid jobs has little or no opportunity for remote work. It is also to be noted that even though India is renowned for its high-tech and financial services but its vast majority of its workforce is employed in retail and agriculture related occupations that cannot be done remotely. Keeping the above aspects in consideration this paper tries to shed some light on the evolution of the concept of work from home and examine the applicability and future of work from home in different industries. The paper also attempts to study how the concept of WFH came as a rescue for organizations after COVID-19 outbreak and examine the pros and cons of remote working by documenting and focusing on the basic facts and figures about working from home.